2022
DOI: 10.4049/jimmunol.2100884
|View full text |Cite
|
Sign up to set email alerts
|

CD11bhigh B Cells Increase after Stroke and Regulate Microglia

Abstract: Recent studies have highlighted the deleterious contributions of B cells to post-stroke recovery and cognitive decline. Different B cell subsets have been proposed on the basis of expression levels of transcription factors (e.g., T-bet) as well as specific surface proteins. CD11b (a-chain of integrin) is expressed by several immune cell types and is involved in regulation of cell motility, phagocytosis, and other essential functions of host immunity. Although B cells express CD11b, the CD11b high subset of B c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 86 publications
0
13
1
Order By: Relevance
“…CD11b/CD18 (Mac‐1, CR3), a multifunctional adhesion and recognition receptor, as β integrins subfamily member, is highly expressed in innate immune cells such as microglia. It plays an important role in the immune response by promoting the recruitment of immune cells and participating in the signal pathway 51 . Research shows that CD11b can recognize lipopolysaccharide and amyloid β protein, α‐Syn, and other PAMPs and DAMPs, which mediate a variety of reactions by transmitting signal molecules downstream 39,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD11b/CD18 (Mac‐1, CR3), a multifunctional adhesion and recognition receptor, as β integrins subfamily member, is highly expressed in innate immune cells such as microglia. It plays an important role in the immune response by promoting the recruitment of immune cells and participating in the signal pathway 51 . Research shows that CD11b can recognize lipopolysaccharide and amyloid β protein, α‐Syn, and other PAMPs and DAMPs, which mediate a variety of reactions by transmitting signal molecules downstream 39,52 .…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in the immune response by promoting the recruitment of immune cells and participating in the signal pathway. 51 Research shows that CD11b can recognize lipopolysaccharide and amyloid β protein, α-Syn, and other PAMPs and DAMPs, which mediate a variety of reactions by transmitting signal molecules downstream. 39,52 In recent decades, the axis of PI3K/NOX2 has become heated research on the aspect of immunoregulation.…”
Section: The Cd11b/pi3k/nox2 Pathway Plays a Role In Neuronal Damage ...mentioning
confidence: 99%
“…Reports on age-related infarct size in the literature are mixed. Many showed that aged mice have significantly smaller infarct sizes ( Liu et al, 2009 ; Manwani et al, 2014 ; Zhao S. et al, 2017 ; Korf et al, 2022 ), while the opposite result has also been recorded ( Shen et al, 2019 ; Liberale et al, 2021 ). Recent data suggests that this difference might be because inflammatory insults that compromise BBB are independent of infarct sizes ( Dénes et al, 2011 ).…”
Section: Aging Exacerbates Neutrophil Pathogenicity In Ischemiamentioning
confidence: 99%
“…While phagocytosis may be beneficial in clearing necrotic tissue, TNF-a is a notorious pro-inflammatory cytokine. 110 Thus, further research on CD11b high B cells is needed prior to therapeutic development for stroke, especially given the overlap between CD11b high B cells, age, and stroke prognoses. As demonstrated, there are several therapies focused on the regulation of T and B-cell activity, and, given these cells apparent role in stroke pathology, these therapies should be tested in patients with stroke.…”
Section: Peripheral Inflammation and Its Contribution To Neuroinflamm...mentioning
confidence: 99%